Fluoride concentration in dentifrices marketed In Argentina. Issue 1 (8th December 2022) - Valadas, Lídia Audrey Rocha; Sorazabal, Ana Laura; Salgado, Pablo Andres; Argentieri, Angela Beatriz; Squassi, Aldo
Abstract: Objectives: The objective of this study was to determine the different forms of fluoride available in dentifrices commercialized in Argentina. Methods: Thirty three different brands of fluoridated dentifrices were purchased in different cities of Argentina. The total fluoride (TF), total soluble fluoride (TSF) and ionic fluoride (IF) of two samples of each brand were analysed (μg F/ml) by ion‐specific fluorine electrodes. Results: A total of 67% of dentifrices showed fluoride content that compromises anti‐caries activity. A total of 54.5% was formulated with sodium fluoride (NaF), 36.3% formulated with sodium monofluorophosphate (MFP), 3% NaF associated with MFP and 9% formulated with stannous fluoride (SnF2). The TF found was less than the amount declared by the manufacturer in all the brands analysed. The concentration of TF found in the fluoride dentifrices ranged from 590.3 to 1381.4 μg/ml F, TSF ranged from 343.1 to 1258.3 μg/ml F, and IF ranged from 13.1 to 913 μg/ml F. Conclusion: The concentrations of TF were below the reported values. TSF and IF were lower than the total fluoride concentration. Most of the samples studied have TSF concentration that compromises anti‐caries effect. Additional studies with a larger number of samples are suggested to obtain more data.